Tagging rs10811661 variant at CDKN2A/2B locus is not associated with type 2 diabetes mellitus in Czech population - Hubáček, J A; Neškudla, T; Klementová, M; Adámková, V; Pelikánová, T (Folia biologica, 2013)
Genome-wide association studies have resulted in the identification of the CDKN2A/2B locus as an important genetic determinant of type 2 diabetes mellitus development. The aim of this study was to investigate the role of this locus in the development of type 2 diabetes mellitus in Czech Slavonic population. Groups of 1,149 type 2 diabetic patients and a group of 2,312 healthy controls, both of Czech origin, were successfully genotyped for the rs10811661 CDK2A/2B tagging polymorphism. The "risky" TT genotype frequencies were almost identical in both examined groups (69.3 % in patients and 68.9 % in controls, P = 0.52; OR [95% CI] = 1.02 [0.87 - 1.19] for TT versus C allele carriers). Similar negative results were obtained when males (P = 0.93) and females (P = 0.23) were analysed separately. We have not confirmed the association between rs10811661 SNP and susceptibility to the type 2 diabetes mellitus in Czech Slavonic population.
Keywords: dospělí; Genetic Loci; Female; Cyclin-Dependent Kinase Inhibitor p15; inhibitor p16 cyklin-dependentní kinasy; Adult; mladý dospělý; ženské pohlaví; jednonukleotidový polymorfismus; modely genetické; Adolescent; Diabetes Mellitus, Type 2; Cyclin-Dependent Kinase Inhibitor p16; inhibitor p15 cyklin-dependentní kinasy; Gene Frequency; lidé; Polymorphism, Single Nucleotide; diabetes mellitus 2. typu; genetická predispozice k nemoci; studie případů a kontrol; Aged, 80 and over; Genetic Predisposition to Disease; frekvence genu; Models, Genetic; Male; Case-Control Studies; Aged; Czech Republic; Young Adult; Česká republika; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; genetické lokusy; Middle Aged; mladiství; Humans